2015
DOI: 10.12693/aphyspola.128.b-37
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Impact Resistance of Steel Fiber Reinforced Concrete on Aggregate Origin

Abstract: In this study, the effect of aggregate origin on impact resistance of steel fiber reinforced concrete was investigated. Using gravel-sized limestone, basalt and natural aggregates of 20 mm of maximum size, normal and steel fiber reinforced concretes were produced. Water/cement ratio and cement dosage of concrete mixtures were 0.5 and 400 kg/m 3 , respectively. It should be noted that superplasticizer and steel fibers were used in concrete production. Hooked-end bundled steel fibers with l/d ratio of 65 and 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This technology can not only increase the tensile strength of concrete under load but also increases impact resistance [2].…”
Section: Introductionmentioning
confidence: 99%
“…This technology can not only increase the tensile strength of concrete under load but also increases impact resistance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Davraz et al studied foam concretes [12]. Many researchers have also done studies on externally fiber reinforced and internally foam filled thin walled tubes, which have high energy absorbing capacity [13][14][15][16][17][18][19][20]. In this study, we have investigated the deformation behavior of PVC-reinforced and pre-formed 6063-T1 aluminum tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the flow and mechanical properties of SCC are dependent on the amount, geometry and distribution of steel fibers in concrete [8,9]. Concrete is brittle in nature, whereas amalgamation of steel fibers provides stability, improves its impact resistance, bond strength and makes it ductile [10][11][12].…”
Section: Introductionmentioning
confidence: 99%